2016
DOI: 10.1177/0269216316666785
|View full text |Cite
|
Sign up to set email alerts
|

From neighbour to carer: An exploratory study on the role of non-kin-carers in end-of-life care at home for older people living alone

Abstract: Support of older people living alone, in particular until the last stage of life, comes along with multiple efforts. Respectful and supporting relationships between professional carers and non-kin-carers are vital to keep non-kin-carers involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Although previous research has shown that caring relationships between older people who are friends and neighbours are characterised by reciprocity based on mutuality (Lapierre & Keating, ; Pleschberger & Wosko, ), our findings show that there are different forms of mutuality in caring relations of older people. The data revealed three mutuality patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous research has shown that caring relationships between older people who are friends and neighbours are characterised by reciprocity based on mutuality (Lapierre & Keating, ; Pleschberger & Wosko, ), our findings show that there are different forms of mutuality in caring relations of older people. The data revealed three mutuality patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Today, some research acknowledges older people's participation in care activities and shows that rather than passively receiving care, older people mutually construct care arrangements with family, friends and formal care (Barken, ) as well as care for their communities (Wiles & Jayasinha, ). Recently, care among older people who are not family has gained increased attention (Pleschberger & Wosko, , ). Typically, care among older people has been understood by examining specific relationships such as friends and neighbours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having ties to neighbors facilitates access to informal aid and reduces the sense of isolation, which can mitigate the problems of maintaining everyday life at a time of advancing age and declining health (Beard et al, 2009;Yen et al, 2009;Oswald et al, 2011;Kalwij et al, 2014;Boerner et al, 2016;Ward et al, 2018). Such challenges include accessing home care (e.g., Nocon and Pearson, 2000;Barker, 2002;Kalwij et al, 2014;Pleschberger and Wosko, 2017), managing depressive symptoms (e.g., Aneshensel et al, 2007;Wight et al, 2009;Wang et al, 2018), maintaining physical functioning (e.g., Balfour and Kaplan, 2002), and achieving other wellbeing outcomes (e.g., Wahl et al, 2009;Morita et al, 2010;Stroope et al, 2017;Gallardo-Peralta et al, 2018). Therefore, older adults' experiences and behaviors in terms of wellbeing, independence, and social integration are closely related to their environments: their neighborhoods (Wahl et al, 2012).…”
Section: Neighborhood Help Among Older Adultsmentioning
confidence: 99%
“…In addition to this, fewer people are available to take on caring roles (Luckett et al, 2014), as families nowadays are often geographically dispersed (such as with emigration from country of origin or adult children moving away for work), and with a greater economic need for women to play a role in the paid workforce (Ireson, Sethi, & Williams, 2018;Williams et al, 2011). Low mortality and lower fertility may also mean that more people are living alone at the end of life (Pleschberger & Wosko, 2017) which brings its own care challenges.…”
Section: Introductionmentioning
confidence: 99%